Accuracy, Bias, and Overgeneralization: Perceived Aggression Guides Threat Detection and Punishment of Female Criminal Offenders. - Morgan, McLean G.; Rule, Nicholas O. (Journal of Nonverbal Behavior, 2025)
Despite centuries of scientific (and sometimes pseudoscientific) interest in identifying criminals, research has not examined the perception and punishment of female criminals. Building on research describing how men's facial appearance relates to juridic outcomes, we therefore investigated criminality inferences, their underlying cues, and hypothetical sentencing judgments from photos of female criminals. Participants categorized violent and nonviolent criminals significantly better than chance (Study 1) and aggression perceptions explained that detection (Study 2). Moreover, women who looked more aggressive received more severe hypothetical (Study 3a) and actual (Study 3b) sentences. Women's facial appearance may therefore play an unintended and incidental role in perceptions of their criminality, illustrating how kernels of truth in social perception promote biases resulting from overgeneralization effects.